2014
DOI: 10.1007/s40136-014-0048-7
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Murine Model of Endolymphatic Hydrops: The Phex Mouse

Abstract: Animal models of endolymphatic hydrops (ELH) provide critical insight into the pathophysiology of Meniere’s disease (MD). A new genetic murine model, called the Phex mouse, circumvents prior need for a time and cost-intensive surgical procedure to create ELH. The Phex mouse model of ELH, which also has X-linked hypophosphatemic rickets, creates a postnatal, spontaneous, and progressive ELH whose phenotype has a predictable decline of vestibular and hearing function reminiscent of human MD. The Phex mouse enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 71 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…Since 2004, the Phex mouse has served as a valuable model to study the pathophysiology of ELH [7,9,24]. In addition to ELH, the Phex gene mutation causes XLH and its characteristic osteomalacia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since 2004, the Phex mouse has served as a valuable model to study the pathophysiology of ELH [7,9,24]. In addition to ELH, the Phex gene mutation causes XLH and its characteristic osteomalacia.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the Phex mouse model and its otologic manifestations has previously been described [7,9,24]. In brief, XLH is caused by a genetic defect in the Phex gene that leads to a dysfunctional Phex protein.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sheykholeslami, et al [35] reported that compared to 10 adult normal mice (P60-P90), the Hyp-Duk/Y mice had either absent or elevated cervical vestibular evoked myogenic potential (cVEMP) with a threshold of a 60 dB normal hearing level. Although the PHEX mutation is not seen in patents of MD, the PHEX murine model (Hyp-Duk/Y) certainly can serve as a viable mouse model that develops typical impaired hearing and balance symptoms for MD [36]. Future studies will enable the PHEX mouse to be a key animal model to hearing research for MD.…”
Section: Genetic Methodsmentioning
confidence: 99%